2014
DOI: 10.1155/2014/930671
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Macular Degeneration in the Aspect of Chronic Low-Grade Inflammation (Pathophysiological ParaInflammation)

Abstract: The products of oxidative stress trigger chronic low-grade inflammation (pathophysiological parainflammation) process in AMD patients. In early AMD, soft drusen contain many mediators of chronic low-grade inflammation such as C-reactive protein, adducts of the carboxyethylpyrrole protein, immunoglobulins, and acute phase molecules, as well as the complement-related proteins C3a, C5a, C5, C5b-9, CFH, CD35, and CD46. The complement system, mainly alternative pathway, mediates chronic autologous pathophysiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 113 publications
2
72
0
Order By: Relevance
“…Chronic innate immune activation contributes to the dysfunction and progressive degeneration of the RPE underlying AMD [2, 4]. Activation of the NLRP3 inflammasome was implicated in mediating the degeneration of the RPE in geographic atrophy [8, 9], the late stage of dry AMD, and the development of choroidal neovascularization [7, 10], the hallmark of neovascular AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic innate immune activation contributes to the dysfunction and progressive degeneration of the RPE underlying AMD [2, 4]. Activation of the NLRP3 inflammasome was implicated in mediating the degeneration of the RPE in geographic atrophy [8, 9], the late stage of dry AMD, and the development of choroidal neovascularization [7, 10], the hallmark of neovascular AMD.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining patients suffer from the neovascular form characterized by choroidal neovascularization. AMD is associated with systemic and local inflammation [24]. Generally, inflammatory processes are activated by cytosolic protein-signaling complexes, termed inflammasomes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AAbs to elastin, heparan sulfate, fibronectin, histone H2B, collagen III, and collagen IV were significantly elevated in sera of AMD patients compared to normal controls [56]. Another study identified more autoantigens, including αβ-crystallin, α-actinin, amyloid, C1q protein, chondroitin, collagen I, III, and IV, elastin, histone H2A and H2B, laminin, vimentin, vitronectin, aldolase C, and pyruvate kinase M2 [16]. AAbs against cyclic nucleotide phosphodiesterase, phosphatidylserine (PS), and proliferating cell nuclear antigen [56], glial fibrillary acidic protein (GFAP), and α-enolase were also documented.…”
Section: Amd and Serological Biomarkersmentioning
confidence: 99%
“…high intake of cholesterol and dietary fats or low intake of dietary vitamin D, zinc, and antioxidants) may also play a role in the pathogenesis of AMD (Clemons et al, 2005;Dasari et al, 2011;Millen et al, 2015;Parekh et al, 2009;Sui et al, 2013). Furthermore, AMD has been recently associated with retinal low-grade inflammation linked by the infiltration and activation of immune cells and production of inflammatory mediators into the site of retinal damage (Nita et al, 2014;Whitcup et al, 2013).…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%